Estimating Pass-Through Rates for the 2022 Tax Reduction on Fuel Prices in Germany - Jonas Dovern; Johannes Frank; Alexander Glas; Lena Müller; Daniel Perico (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze the effectiveness of the German tax reduction on fuel prices ('Tankrabatt') that was introduced for three months, starting on 1 June 2022. Using the synthetic control method to compare actual prices of gasoline and diesel to those in a counterfactual situation without the tax reduction, we find that the tax reduction has been completely passed on to consumers for most of the three months. In early June, it took approximately two weeks for the full pass-through to take effect. Moreover, pass-through rates started to decline in August while the tax reduction was still in place. We observe an upward price jump smaller than the size of the expiring tax reduction at the start of September. Our results are robust to different approaches of constructing the synthetic control group.
Keywords: C22; E31; E65; H22; Q41; 330; fuel; gasoline; diesel; taxes; synthetic control group